New data on Labronemella labiata Andrássy, 1985 (Dorylaimida: Qudsianematidae) from Iran, with SEM study and a compendium of the genus - Peña-Santiago, Reyes; Abolafia, Joaquín; Pedram, Majid (Zootaxa, 2012)
Labronemella labiata, the type species of its genus, is described after studying an Iranian population. An emendeddiagnosis of the species is provided, with new morphological and morphometrical features. The lip region, the mostdistinctive character of Labronemella is observed under SEM by the first time and its detailed morphology elucidated.Anterior surface (oral field) appears distinctly sunken and with its inner (perioral) area differentiated in six large, separatedliplets protruding on oral field. The lateral, perioral liplets are trapezoidal and visibly larger than subdorsal and subventralones, which are triangular, consequently the lip region shows a bi-radial symmetry. Inner labial papillae migrate to themargin of labial disc, being located close to outer labial and cephalic papillae. The systematics of Labronemella is brieflydiscussed, including diagnosis, updated list of species, key to their identification as well as a compendium of their main measurements and morphometrics.